The Optimal and Actual Use of EVA versus Earnings in Actual Compensation - Gerald T. Garvey; Todd T. Milbourn (Claremont McKenna College, Department of Economics, 2000)
Proponents of EVA and related 'shareholder value' measures intend to replace earnings and to supplement stock returns by including their own measures in managerial compensation schemes. Stern Stewart's EVA appears to be the most widely recognized measure. However, there are not very many firms have explicitly adopted such schemes. One obvious reason, which we account for explicitly, is that they are not appropriate for all firms. An additional, less obvious fact, is that firms can directly or even indirectly mimic EVA measures. Firms such as Clorox and O.M. Scott use their own performance measures, which are arguably variants of EVA. In this paper, we use publicly available estimates of firm level EVA and examine whether firms pay according to it regardless of their explicit policies. This research approach captures the fact mentioned above, that firms can do home-made EVA performance evaluation. We adapt the technique of Garvey and Milbourn (2000) to model the optimal weight placed on EVA at the firm level. There is enormous cross-sectional heterogeneity in the estimated 'value-added' of EVA for various firms. With our estimates of optimal weights, we verify empirically that compensation paid to the top five executives in over 2,000 firms is highly consistent with our optimal compensation arrangements.
Keywords: 330